Predictors of Routine Dental Check-up Among Male Adolescents in Saudi Arabia - Muhammad Ashraf Nazir (Acta Stomatologica Croatica, 2019)
Objective: To evaluate the association of socioeconomic factors and self-perceived oral conditions with routine dental check-up among male adolescents. Methods: This cross-sectional study was conducted on male children (grade 10-12) from public schools in different cities of the Eastern province of Saudi Arabia. A multistage random sampling was used for the recruitment of study participants. A piloted questionnaire translated into the Arabic language was used for data collection. Results: There were 586 students with mean age 16.86±0.87 years. The prevalence of routine dental visit within last year was 18.9%. Half of the entire sample had dental cavities (50.5%) and tooth sensitivity (50%) followed by dental pain (42.2%). Bivariate analyses found that the children with dental cavities (OR 0.4, 95% CI 0.26, 0.61), dental pain (OR 0.63, 95% CI 0.41, 0.97), and malodor (OR 0.41, 95% CI 0.23, 0.71) had significantly lower odds of routine dental visits than those without these conditions. The final model of multivariable logistic regression showed that dental cavities (OR 0.42, 95% CI 0.27, 0.66) and malodor (OR 0.45, 95% CI 0.25, 0.78) were significantly associated with lower likelihood of visiting dental office for a regular dental check-up. No significant influence of socioeconomic factors on routine dental attendance was observed. Conclusions: A small proportion of children performed routine dental visits. The children with dental cavities and malodor were less likely to perform routine dental visits. The awareness about the importance of regular dental check-up should be raised to reduce the burden of oral diseases in schoolchildren.